12- to 14-month-olds expect unconstrained agents to act efficiently: event-related potential (ERP) evidence from the head-touch paradigm - Langeloh, Miriam; Buttelmann, David; Pauen, Sabina; Höhl, Stefanie (Developmental psychology, 2020)
Behavioral research has shown that 12- but not 9-month-olds imitate an unusual and inefficient action (turning on a lamp with one's forehead) more when the model's hands are free. Rational-imitation accounts suggest that infants evaluate actions based on the rationality principle, that is, they expect people to choose efficient means to achieve a goal. Accordingly, infants' expectations should be violated when observing inefficient actions. However, this has yet to be clearly tested. Here, we conducted three electrophysiological experiments to assess infants' neural indices of violation of expectation (VOE) when observing hand- and head-touch actions. We presented infants with video sequences showing a model whose hands were either free (Experiments 1 and 3) or restrained (Experiment 2). Subsequent images depicted a person turning on a lamp or a toy soundbox using her hand or head. We analyzed the Negative central (Nc) component, associated with the amount of attentional engagement, and the N400 component, reflecting semantic violations. In line with rational-imitation accounts, results revealed that 12- to 14-month-olds (Experiment 1) but not 9-month-olds (Experiment 3) were surprised while observing an inefficient, hands-free, head touch, as indicated by an increased Nc amplitude and an N400-like component. In contrast, infants did not show differences in our measures of VOE between head- and hand-touch outcomes when the model's hands were restrained (Experiment 2). Thus, we suggest that 12- to 14-month-olds incorporate the action context when evaluating action outcomes. (PsycInfo Database Record (c) 2020 APA, all rights reserved).
Gesehen am 10.08.2020